Policy Dialogue: Black Teachers of the Past, Present, and Future. (February 2021) - Ladson-Billings, Gloria; Anderson, James D.
Abstract : In the second half of the twentieth century, the ranks of Black teachers and school administrators declined precipitously. Today, less than 7 percent of American teachers are Black. This loss has had a number of consequences for schools and communities, but perhaps especially for Black students. As recent research has found, Black students benefit socially and academically from having a Black teacher, are less likely to be suspended or expelled, and are more likely to enroll in college. For this inaugural policy dialogue, the HEQ editors asked Gloria Ladson-Billings and James D. Anderson to reflect on the past, present, and future of the Black teacher corps. Their wide-ranging exchange explores the various roles of educators, the legacy of segregation, the role of policy, and the Black experience. They close with a provocative list of research questions for emerging and established scholars to consider.